AN EMPIRICAL INVESTIGATION OF FACTORS AFFECTING STUDENT SATISFACTION: A CASE STUDY OF A SRI LANKAN PRIVATE HIGHER EDUCATIONAL INSTITIUTE (Proceedings of the International Conference on Social Sciences, 2018)
Satisfying customer need is a key to obtain sustainable competitive advantage in the business world. Due to high competitiveness in Sri Lankan private higher education industry “Student Satisfaction” is a crucial success factor for institutes to remain in the industry. Therefore there is a growing need to understand factors that affect satisfaction of students of private sector higher educational institutes. This study empirically examines factors affecting student satisfaction of Business Management undergraduates’ of a leading Sri Lankan private higher educational institute. Previous research done under various environments has recommended a variety of factors affecting user satisfaction. This study developed a model which adopted recognition of the programme, quality of the teaching and academic administration from HEDPERF model of Firdaus (2005) with two other dimensions facilities and skill match taken from other studies. The study was conducted in correlation with UN Sustainable Development Agenda – 2030 (Aim No-4
Keywords: undergraduate student; Business management; Student Satisfaction; Private Higher education